Thailand : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the assessment on observance of standards and codes on fiscal transparency for Thailand. The assessment reveals that Thailand meets requirements of the fiscal transparency code in many respects and exceeds them in a few cases. The legal framework underlying public finance is broadly sound. The budget process is well specified. The legal framework for public debt management is clear, and reporting of public debt is transparent. The National Counter-Corruption Commission and the Office of Auditor General provide important independent checks on the integrity of public finances.